TECHNOLOGICAL CONTENT KNOWLEDGE (TCK) ANALYSIS IN ONLINE LEARNING ASSISTED BY C-MAP TOOLS ON STATIC ELECTRICITY - Tsabitamia Irba; Nurita Apridiana Lestari (Universitas Negeri Medan, 2021)
The aims of the study were to determine students' abilities about Technological Content Knowledge (TCK) assisted by C-Map Tools on static electricity material. The method in this research uses assignments and filling out questionnaires. The sample used in this research is class XII IPA 1. Data were collected by average score of student response questionnaire and average of students six group for rubric assessment C-Map Tools by Suprapto, 2018. Data analysis using descriptive analysis with the average score of the student response questionnaire and the average score rubric assessment C-Map Tools. Students' abilities regarding TCK were obtained from the results of student response questionnaires which contained 3 aspects, namely display, material, and advantage. The average in these three aspects is 77.4%. Students’ skill to make concept mapping in the topic of static electricity through C-Map Tools application achieved with a 75.08% of 100% with a good category. Students are able to connect concepts to one another by using the C-Map Tools application. There is also a limitation in this research, that many students did not include focus questions on their c-map tools.